Diet and seed dispersal potential of the white-lined bat, Platyrrhinus lineatus (E. Geoffroy, 1810), at a site in northeastern Brazil. (2nd January 2016) - Silvestre, Saulo M.; da Rocha, Patrício A.; da Cunha, Mônica A.; Santana, José Paulo; Ferrari, Stephen F.
ABSTRACT: This study provides insights into the dispersal potential of Platyrrhinus lineatus and its role in habitat regeneration. The study site was an urbanized area in northeastern Brazil. Fecal samples were collected at the roost of a colony during 13 months. Seven species were present in the samples, three of which were exotic. Cecropia glaziovii, Solanum stipulaceum and Coccothrinax barbadensis predominated in the diet of the colony. The large numbers of seeds of pioneer species, and the exotic species present in the diet of the colony emphasize the role of P. lineatus in the regeneration of habitats, and its ecological flexibility.